Speech Situation Analysis Allfy Rev Propose for Linka in The Twilight and Morning Music Videos - Amilia Buana Dewi Islamy (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Speech situation needs to be understood as the cause of the occurrence of speech events in which there are certain speech acts. Speech situation analysis is important to analyze because it is related to understanding the purpose of speech. The purpose of analyzing the situation of the speech is to minimize misunderstandings in communication by understanding. By analyzing the situation of speech can be determined the type of speech act. In addition, the intent will be understood with rational reasons. Music trends that combine with personal life aside from being a place for expressing the expression of the author can also attract the market. The themes of love become the theme of choice by people in early adulthood. Responding to the video, there are two contradictory assumptions about marrying at a young age, some consider it positive and some consider it negative. This study aims to explain through the analysis of the speech situation, that the speaker has a specific purpose. That purpose must be understood in full so that the community is able to assess objectively. The research approach is a pragmatic approach and a qualitative descriptive approach. The data of this research is in the form of speech fragments which are suspected to be directive speech acts. The data source in this study is the speech contained in the music video Dusk and Morning. Data collection techniques using the technique of free and involved involved proficient and note taking techniques. The data analysis method is in the form of a matching method, while the method of presenting the results of data analysis uses the informal method. From this research it is expected to find the meaning in a music video and the value of mutual respect that will be useful with references in life. Abstrak Situasi tutur perlu dipahami sebagai penyebab dari munculnya peristiwa tutur yang di dalamnya terdapat tindak tutur tertentu. Analisis situasi tutur menjadi penting untuk dianalisis karena berkaitan dengan pemahaman maksud dari tuturan. Tujuan dari menganalisis situasi tutur adalah untuk meminimalkan kesalahpahaman dalam berkomunikasi dengan cara memahami. Dengan menganalisis situasi tutur dapat ditentukan jenis tindak tutur. Selain itu, maksud akan dipahami dengan alasan yang rasional. Tren musik yang digabungkan dengan kehidupan pribadi selain sebagai wadah pengungkapan ekspresi pengarangnya, juga dapat menarik pasar. Tema-tema cinta menjadi tema pilihan oleh orang-orang yang berada pada usia dewasa awal. Terhadap video tersebut terdapat dua anggapan yang bertentangan tentang menikah di usia muda, ada yang menganggapnya positif dan ada yang menganggapnya negatif. Penelitian ini bertujuan untuk menjelaskan melalui analisis situasi tutur, bahwa penutur memiliki maksud tertentu. Maksud itu harus dipahami secara utuh agar masyarakat mampu menilai secara objektif. Pendekatan penelitian ini berupa pendekatan pragmatik dan pendekatan deskriptif kualitatif. Data penelitian ini berupa penggalan tuturan yang diduga merupakan tindak tutur direktif. Sumber data dalam penelitian ini yaitu tuturan yang terdapat pada video musik Senja dan Pagi. Teknik pengumpulan data menggunakan teknik simak bebas libat cakap dan teknik catat. Metode analisis data berupa metode padan, sedangkan metode penyajian hasil analisis data menggunakan metode informal. Dari penelitian ini diharapkan dapat menemukan maksud dalam sebuah video musik dan nilai saling menghargai yang akan berguna dengan referensi dalam kehidupan. Kata kunci: situasi tutur, tindak tutur direktif, ajakan,konteks tuturan, melamar